Challenges and pitfalls of experimental bariatric procedures in rats - Fischer, Lars; Clemens, Gabriella; Gehrig, Tobias; Kenngott, Hannes Götz; Becker, Kristianna; Bruckner, Thomas; Gutt, Carsten N.; Büchler, Markus W.; Müller, Beat P. (Obesity facts, 2012)
The impact of Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) on obesity and obesity-related diseases is unquestionable. Up to now, the technical descriptions of these techniques in animals/rats have not been very comprehensive. Methods: For SG and RYGB, operating time, learning curve, and intraoperative mortality in relation to weight of the rat and type of anesthesia were recorded. Furthermore, a review of the literature on experimental approaches towards SG and RYGB in rats was carried out, merging in a detailed technical description for both procedures. Results: The data presented here revealed that the mean operating time for SG (69.4 ± 22.2 min (SD)) was shorter than for RYGB (123.0 ± 20.7 min). There is a learning curve for both procedures, resulting in a reduced operating time of up to 60% in SG and 35% in RYGB (p < 0.05; t-test). However, with increased weight, operating time increases to about 80 min for SG and about 120 min for RYGB. Obese rats have an increased intraoperative mortality rate of up to 50%. After gaseous anesthesia the mortality can be even higher. The literature search revealed 40 papers dealing with SG and RYGB in rats. 18 articles (45%) contained neither photographs nor illustrations; 14 articles (35%) did not mention the applied type of anesthesia. The mortality rate was described in 15 papers (37.5%). Conclusion: Experimental obesity surgery in rats is challenging. Because of the high mortality in obese rats operated under gaseous anesthesia, exercises to establish the techniques should be performed in small rats using intraperitoneal anesthesia.